2018
DOI: 10.17116/neiro201882373
|View full text |Cite
|
Sign up to set email alerts
|

The transpalpebral keyhole approach in surgery of orbital cavernomas: a case report and literature review

Abstract: The transpalpebral keyhole approach can be an excellent alternative to traditional approaches to orbital cavernomas. This approach demonstrated its efficacy and safety in skull base surgery and provided excellent functional and cosmetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…We assessed the functional and cosmetic outcomes, surgical complications and concluded that TPA could be successfully performed as an alternative method to traditional extended approaches and endoscopic routes in the skull base surgery. [38][39][40] In this report, we presented outcomes in 15 patients diagnosed with TSM. A surgical approach was selected with critical assessment of facial and bone anatomy, sizes of the tumor.…”
Section: Discussionmentioning
confidence: 98%
“…We assessed the functional and cosmetic outcomes, surgical complications and concluded that TPA could be successfully performed as an alternative method to traditional extended approaches and endoscopic routes in the skull base surgery. [38][39][40] In this report, we presented outcomes in 15 patients diagnosed with TSM. A surgical approach was selected with critical assessment of facial and bone anatomy, sizes of the tumor.…”
Section: Discussionmentioning
confidence: 98%
“…In the past, neurosurgeons have often used approaches that can be accompanied by negative cosmetic and functional outcomes. 1 In recent years, minimally invasive skull base surgery has evolved significantly. 2 Skull base surgeons sometimes pair with an orbital surgeon when accessing orbital pathology.…”
Section: Introductionmentioning
confidence: 99%